ChemInform Abstract: Nickel‐Catalyzed and Benzoic Acid‐Promoted Direct Sulfenylation of Unactivated Arenes. Issue 27 (18th June 2015) - Yang, Ke; Wang, Yuqi; Chen, Xinyong; Kadi, Adnan A.; Fun, Hoong‐Kun; Sun, Hao; Zhang, Yan; Lu, Hongjian
Abstract Depending on substitution pattern, N‐(2‐(pyridin‐2‐yl)propan‐2‐yl)arylamides are regioselectively mono‐ and/or bis‐arylsulfenylated with diaryl disulfides (II) and (IX) in the ortho‐position(s) next to the amide group.